Effects of land use types and spatial heterogeneity on soil microbial biomass and activity along environmental gradients in Austral ecosystems - Toledo, Santiago; Martínez Pastur, Guillermo José; Rodríguez‑Souilla, Julián; Peri, Pablo Luis (Elsevier, 2025)
Different land use systems can alter the structure and function of soil microorganisms, affecting microbialmediated processes and potentially undermining consequences for soil fertility and ecosystem health. The effects of land use types (LUTs) on soil microbial attributes remain poorly understood in ecosystems. Therefore, the objectives were: (i) to evaluate the responses of microbial biomass carbon (MBC) and nitrogen (MBN), MBC: MBN, soil basal respiration (SBR), microbial metabolic quotient (qCO2), and microbial quotient (qMC) to different LUTs, including primary forests (PF), silvopastoral systems (SPS) and grasslands, across an environmental gradient from coastal to inland sites of Southern Patagonia; and (ii) to assess the influence of Nothofagus antarctica tree canopies (canopy vs inter-canopy) on these microbial attributes. SPS maintained similar values of MBC, MBC:MBN, and qMC compared to PF, but with significant increasing SBR (40%) and qCO2 (55%) values. Grasslands decreased MBN (71 mg kg− 1), SBR (44 mg C kg− 1), and qCO2, but increased the MBC:MBN compared with PF. Inland sites at higher altitudes showed reductions in MBC (45%), MBN (28%), and MBC:MBN, and increases in qCO2 (77%) compared to inland and coastal areas at lower altitudes. Moreover, microbial variables (MBC, MBN, SBR, qCO2, and qMC) were consistently higher under tree canopies than in inter-canopy areas. These findings highlight the importance of conserving forest stands under SPS use to sustain soil microbial functions. Soil microbial attributes could serve as sensitive and effective bioindicators of soil quality and health, offering valuable tools for land use monitoring in ecosystems.